OPTIMIZING MODERN AGRICULTURAL PRODUCTS THROUGH A DRIP IRRIGATION SYSTEM IN THE PAPUA FARM FARMERS GROUP, AIMAS REGENCY, SOUTHWEST PAPUA - Athirah, Aldila Mawanti; Aprianto, Aci; Sabarudin, Dian Nitari Ribanor; Risdianti, Tri Sindi; Suciati, Suciati; Mawar, Mawar; Badali, Muhammad Imam Mudin (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Increasing agricultural productivity in Eastern Indonesia, particularly in Aimas District, Sorong Regency, is a strategic step in supporting local food security and farmer welfare. Papua Farm, a pioneer in hydroponic lettuce cultivation in Papua, faces challenges such as limited water, climate fluctuations, and limited access to modern agricultural technology. A community service program titled "Optimizing Modern Agricultural Products through Drip Irrigation Systems at the Papua Farm Farmer Group, Aimas District, Southwest Papua" was implemented to address these challenges. The drip irrigation system was chosen because it can channel water and nutrients directly to the plant's root zone, reduce water loss due to evaporation, and increase fertilizer efficiency through fertigation. The program was implemented using a participatory approach through stages of socialization, training, demonstration plot installation, mentoring, and evaluation. Results showed a water use efficiency of up to 40%, a reduction in labor costs of Rp1,000,000 per season, and an increase in harvest productivity of around 25% with more uniform crop quality. In addition to technical aspects, this program also increases farmers' knowledge capacity, strengthens group institutions, and opens market opportunities through agribusiness digitalization. Thus, the application of the drip irrigation system has proven effective as a model of modern, sustainable agricultural technology and is worthy of being replicated in other areas with similar conditions.